Bioaccumulation and bioconcentration of carbamazepine and other pharmaceuticals in fish under field and controlled laboratory experiments. Evidences of carbamazepine metabolization by fish - Valdés, María Eugenia (2016)
There is a growing interest in evaluating the presence of pharmaceutical residues and their metabolites in aquatic biota. In this study, twenty pharmaceuticals, including carbamazepine (CBZ) and two metabolites, were analyzed in homogenates of two fish species (Gambusia affinis and Jenynsia multidentata) captured in polluted areas of the Suquía River (Córdoba, Argentina). The twenty target pharmaceuticals were found in G. affinis, while only fifteen were detected in J. multidentata. We observed a noticeable difference in the accumulation pattern of both fish species, suggesting different pathways for the bioaccumulation of polar pharmaceuticals in each fish. In order to investigate uptake and tissue distribution of pharmaceuticals, a detailed study was performed under controlled laboratory conditions in J. multidentata, exposed to CBZ. CBZ and two of its metabolites (carbamazepine-10,11-epoxide – CBZ-EP and 2-hydroxycarbamazepine – 2-OH-CBZ) were monitored in five organs of fish under laboratory exposure. To our knowledge, this is the first report on the presence of CBZ and its metabolite 2-OH-CBZ in gills, intestine, liver, brain and muscle of fish, while the metabolite carbamazepine-10,11-epoxide (CBZ-EP) was detected in gills and muscle. A ratio CBZ-EP/CBZ close to 0.1 suggests that gills and muscle of J. multidentata could metabolize CBZ through the CBZ-EP pathway. Our results reinforce the need of analyzing multiple species to account for the environmental impact of pollutants, negating the simplification of a single, “representative model” during ecotoxicological biomonitoring. To our knowledge, the biotransformation of CBZ to its metabolites (CBZ-EP, 2-OH-CBZ) in fish, under controlled laboratory in vivo exposures, is reported for the first time.